The reproductive biology of warty sea cucumber, Neostichopus grammatus Clark (Holothuroidea: Echinodermata) under natural and integrated multi-trophic aquaculture (IMTA) conditions in the Eastern Cape Province, South Africa - Senekal, Heleen Ester (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science)
This study investigated the reproductive cycle of the warty sea cucumber, Neostichopus grammatus, in the wild and in a farming environment, to test its suitability for co-culture with abalone Haliotis midae in an IMTA system. The research formed part of a broader EU H2020 program, Aquavitae, and was conducted at Wild Coast Abalone in South Africa. The study investigated several environmental parameters, such as temperature, day length, and substrate, to determine if these have any effects on the gonadal development and reproductive cycle. The natural gametogenic cycle of wild warty sea cucumbers was determined by monitoring the Gonadosomatic Index (GI) values monthly for a period of 16 months. The GI index was validated by means of other maturity assessment techniques including measurement of the size and colour of the gonads, oocyte diameter measurements and gonad histology sections. Wild collected sea cucumbers were maintained in abalone farm rearing tanks on a diet of abalone feed and faecal waste for a period of 10 months, with GI values being determined monthly. The wild and farmed sea cucumber GI data was correlated with environmental parameters. Seasonal water temperature was strongly correlated with the GI values of wild warty sea cucumbers, suggesting that water temperature likely influences gonadal development. Sea cucumbers matured sexually during colder months (May to September) and spawned from September to February, during summer. The results of oocyte measurements, macroscopic and microscopic analyses, and histological analyses in combination with the GI values, provides a practical indicator of sexual maturity for captive breeding purposes. Farmed warty sea cucumbers followed the same annual reproductive cycle as wild sea cucumbers, however they came into spawning condition approximately one month later than wild conspecifics. As the farm water temperature was significantly higher than the ambient ocean water temperature, it was hypothesised that this may have affected the gonadal development of the farmed sea cucumbers. Furthermore, the farm-reared sea cucumbers lost weight and condition, indicating a nutritional deficiency. Previous studies indicated that the presence of a sand sediment facilitated the assimilation of organic detrital matter by sea cucumbers. An additional trial was thus set up to determine the effect of a sand sediment and cooler ambient temperature on the growth and gonadal development of the warty sea cucumbers. The growth and GI values of sea cucumbers in the cool water treatment did not differ significantly from the ambient temperature control groups. However, the addition of a sand substrate to the sea cucumber tanks had a significant positive growth effect on sea cucumber body mass and GI values. Sea cucumbers fed a diet of abalone waste material on the sand substrate exhibited final average GI values of 2.99 % (SE Â±0.56). In contrast, sea cucumbers kept in bare tanks and only received abalone waste as food had significantly lower average GI values of 1.36 % (SEÂ±0.2). This suggests that the provision of a sand sustrate in sea cucumber rearing containers is essential for the adequate nutrition and gonadal development. The results of this study indicate that the warty sea cucumber is a promising candidate for inlcusion in an IMTA system with South African perlemoen abalone.
Keywords: Sea cucumbers -- South Africa -- Eastern Cape; Sea cucumbers Reproduction; Gonads; Gonadosomatic Index; Integrated aquaculture; Abalone culture; Sea cucumbers Effect of temperature on; Marine sediments